A Study of Force and Position Tracking Control for Robot Contact with an Arbitrarily Inclined Plane. (25th January 2013) - Bosheng, Ye; Bao, Song; Zhengyi, Li; Shuo, Xiong; Xiaoqi, Tang
This paper proposes an adaptive impedance control method for a robot's end-effector while it slides steadily on an arbitrarily inclined panel; it concentrates on robot force position tracking control for the inclined plane with an unknown normal direction and varying environmental damping and stiffness. The proposed control strategy uses the Recursive Least Squares (RLS) algorithm to estimate environmental damping and stiffness parameters during the impact-contact process between the robot and the environment. It achieves the expected posture adjustment of the robot's end-effector based on the measured contact torques and, during the robot's end-effector's sliding on the inclined plane, a fuzzy control is developed to adjust the robot impedance model parameters on-line and adaptively for changes in environmental damping and stiffness. The designed robot force position control method is robust to the changes of the environmental parameters but the implementation of the proposed control algorithms is simple. Finally, experiments demonstrate the effectiveness of the proposed method.